Development and Validation of a Novel Prognostic Model for Overall Survival in Newly Diagnosed Multiple Myeloma Integrating Tumor Burden and Comorbidities - Jia, Shuangshuang; Bi, Lei; Chu, Yuping; Liu, Xiao; Feng, Juan; Xu, Li; Zhang, Tao; Gu, Hongtao; Yang, Lan; Bai, Qingxian; Liang, Rong; Tian, Biao; et al. (Frontiers in Oncology, 2022)
Background: Multiple myeloma (MM) is a highly heterogeneous disease with enormously variable outcomes. It remains to be a major challenge to conduct a more precise estimation of the survival of MM patients. The existing stratifications attached less importance to the prognostic significance of comorbidities. In the present study, we aimed to develop and validate a novel and simple prognostic stratification integrating tumor burden and comorbidities measured by HCT-CI. Methods: We retrospectively enrolled 385 consecutive newly diagnosed Multiple myeloma (NDMM) patients in Xijing Hospital from January 2013 to December 2020. The cohort between January 2016 to December 2020 was selected as development cohort (N=233), and the cohort between January 2013 to December 2015 was determined as validation cohort (N=152). By using LASSO analysis, univariate and multivariable Cox regression analyses, we developed the MM-BHAP model in the way of nomogram composed of β2-MG, HCT-CI, ALB, and PBPC. We internally and externally validated the MM-BHAP model and compared it with ISS stage and R-ISS stage. Results: The MM-BHAP model was superior to ISS stage and partially better than R-ISS stage according to time-dependent AUC, time-dependent C-index, DCA, IDI and continuous NRI analyses. In predicting OS, only the MM-BHAP stratification clearly divided patients into three groups while both the ISS stage and R-ISS stage had poor classifications in patients with stage Ⅰ and stage Ⅱ. Moreover, the MM-BHAP stratification and the R-ISS stage performed well in predicting PFS, but not for the ISS stage. Besides, the MM-BHAP model also applied to the patients with age ≤ 65 or age > 65 and with or without HRCA and could enhance R-ISS or ISS classifications. Conclusions: Our study offered a novel simple MM-BHAP stratification containing tumor burden and comorbidities to predict outcomes in the real-world unselected NDMM population.